1979
DOI: 10.1177/002216787901900309
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic Psychology as Liberal Ideology: the Socio-Historical Roots of Maslow's Theory of Self-Actualization

Abstract: Humanistic psychology can best be understood within its cultural context. It is within this context that I advance the claim that humanistic psychology in general, and Maslow's theory of self-actualization in particular, have their genesis in liberalism.My purpose in this article is to try and reveal both the nature and consequences of the link between humanistic psychology and the liberal tradition using Maslow's theory as a concrete case for analysis. This analysis is part of a larger goal to examine the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Re-casting Maslow and Rogers' earlier concept of an actual-self, more in line with Heidegger's existential being constituted by historical, social, cultural, political, and economic forces, would inoculate humanistic psychology against its various detractors, who argue that its conceptualisation ofthe self represents a form of essentialism (Cosgrove, 2007;Geller, 1982, Neher, 1991 and/or political expediency (Buss, 1979;Brinkman, 2008;Carrette, 2003;Malone, 2007;Shaw & Colimore, 1988). By disciplining the self to history and language, the self is not only conceived of as a conscious process of becoming, it also comes to reflect the on-going changes in societal conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Re-casting Maslow and Rogers' earlier concept of an actual-self, more in line with Heidegger's existential being constituted by historical, social, cultural, political, and economic forces, would inoculate humanistic psychology against its various detractors, who argue that its conceptualisation ofthe self represents a form of essentialism (Cosgrove, 2007;Geller, 1982, Neher, 1991 and/or political expediency (Buss, 1979;Brinkman, 2008;Carrette, 2003;Malone, 2007;Shaw & Colimore, 1988). By disciplining the self to history and language, the self is not only conceived of as a conscious process of becoming, it also comes to reflect the on-going changes in societal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It mobilised human resources by calling for the uncovering of productive values, talents, and skills (Malone, 2007). The idea ofthe actualising tendency allows the individual to maintain an illusion of self-hood, agency, and freedom, while ensuring efficient, rational, enterprising, and productive members of society (Buss, 1979;Carrette, 2003;Malone, 2007;Shaw &Colimore, 1988). Foucault's (1983, p. 212) concept ofthe subject is composed of two basic dimensions: (1) the subject of power, knowledge, and discourse influenced by governmental systems and their institutional practices, and (2) the subject tied to an identity by a conscience or self-knowledge.…”
Section: He Self In Humanistic Psychologymentioning
confidence: 99%
“…Maslow is well known for conceptualization of a ''hierarchy of human needs'', which presents values from the viewpoint of human fundamental needs [32]. His concern was how people can self-actualize, and thereby overcome negative aspects of humanity.…”
Section: History Of Axiologymentioning
confidence: 99%
“…Critics of this perspective have argued that the humanistic movement is exceedingly individualistic and overly optimistic about human potentialities and how actualizing these individual potentialities can contribute to social change ( e g , Buss, 1979;Campbell, 1984;Geller, 1982;Marien, 1983aMarien, , 1983bSmith, 1978Smith, , 1982South, 1984). Smith (1982) suggested that the humanistic movement fosters a "superficial, bland optimism , .…”
mentioning
confidence: 99%